Energy performance assessment of an intelligent energy management system. (March 2016) - Gangolells, Marta; Casals, Miquel; Forcada, Núria; Macarulla, Marcel; Giretti, Alberto
Abstract: Although energy management systems are expected to result in decreased energy consumption, it is important not to overlook the energy used until commissioning (including raw materials acquisition, manufacturing and transportation) and during the usage phase (including operation and maintenance). This paper examines the energy performance of an intelligent energy management system for underground metro stations. The results show that the energy management system has high energy performance in terms of energy payback time and energy return factor, due to its low cumulative energy demand and its potential for energy savings. When we assumed that the lifespan of energy management systems may vary between 5 and 10 years, their cumulative energy demand was found to range between 505, 316 and 852, 493 MJp eq. In all cases, the operating energy was found to far outweigh the embodied energy (68–81%). The energy management system was implemented in a pilot underground station and was found to provide an energy saving of 13.2±1.1% of the total energy consumption of the pilot station. The energy payback time of the energy management system for underground stations was found to range between 40 and 55 days. Consequently, the system pays back between 33 and 91 times the energy invested in it. The results of this research provide valuable information for stakeholders in the energy management systems industry, as they contribute to ascertaining the sustainability of products.